Exclusion of Polymorphisms in Carnosinase Genes (CNDP1 and CNDP2) as a Cause of Diabetic Nephropathy in Type 1 Diabetes : Results of Large Case-Control and Follow-Up Studies - WANIC, Krzysztof; PLACHA, Grzegorz; DUNN, Jonathon; SMILES, Adam; WARRAM, James H; KROLEWSKI, Andrzej S (Diabetes (New York, N.Y.), 2008)
Recently, an association was found between diabetic nephropathy and the D18S880 microsatellite, located in the carnosinase gene (CNDP1) on chromosome 18q. Alleles of this microsatellite encode for a variable number of leucine residues (from four to seven) in the leader peptide of the carnosinase precursor. The frequency of subjects homozygous for the five leucines was higher in control subjects than in case subjects in studies focusing on type 2 diabetic patients. To test whether this finding can be extended to type 1 diabetic patients, we carried out a comprehensive study on association between diabetic nephropathy and the D18S880 microsatellite and 21 additional SNPs that tagged the genomic region containing CNDP1 and CNDP2. Overall, 1,269 Caucasian patients with type 1 diabetes were included in the study, including 613 patients with normoalbuminuria and a long duration of diabetes, 445 patients with persistent proteinuria, and 211 patients with end-stage renal disease (ESRD). All patients were genotyped for selected polymorphisms, the associations with diabetic nephropathy were tested by a chi(2) test, and odds ratios were calculated. We did not find any significant association between diabetic nephropathy and any examined genetic markers. The negative findings of the case-control study were supported further by negative findings obtained from the 6-year follow-up study of 445 patients with persistent proteinuria, during which 135 patients developed ESRD. Our large, comprehensive study did not find an association between the D18S880 microsatellite or any other polymorphisms in the CNDP2-CNDP1 genomic region and susceptibility for diabetic nephropathy in type 1 diabetes.